The study of factors affecting the formation and transformation of university in Iran since the establishment of Tehran University - monireh sohrabi; mohammad yamani douzi; maghsood farasatkhah; hassan hazrati (Shahid Chamran University of Ahvaz, 2021)
Introduction:The university system is one of the subsystems and component of the higher education system and the social system; hence, it is influenced by other higher education institutions, the educational system of the country and peripheral devices such as political, economic, social and cultural systems. Many thinkers and educators, who advocate new perspectives on educational reform, believe that policy making and planning in order to redefine the past and present performance of educational systems in each country should be done in the light of the historical background of educational developments and the analysis of the current state of the educational system, because in this case, it is possible to discover the factors that led to the decline of cultural and scientific activities and the formation of the current educational methods with an open and comprehensive view. This research aims to study "the factors affecting the formation and transformation of the university in Iran since the establishment of the University of Tehran as the first Iranian official to date". Methods:This research was done by using thematic analysis method consisting of three stages of descriptive coding, interpretive coding and content development. In order to achieve the purpose of the research, semi-structured interviews were conducted with experts and those who had experience in higher education. Results:The findings of the analysis of the content indicate that several factors have contributed to the formation of the university in Iran. History of the University in Iran from interviewee's views, six distinct courses can be divided into different policies and approaches to higher education. Discussion:In all these periods, many political, economic, social, cultural, ideological and scientific factors have affected the changes and changes in the university. Findings show that there are no significant differences between Iranian universities. The reason for this is the lack of creativity in the management of higher education system on the one hand and centralization on the other. Making any structural, quantitative and qualitative changes in the higher education system of the country should be based on deep sociological, economic, political and cultural studies and its growth and expansion in line with the needs and developments created in these areas. By adopting legal mechanisms and proper culture, the effects of severe political and economic factors and its destructive effects on the higher education system were prevented. The question is, "